Diagnóstico sorológico de herpesvírus bovino 1 e 5: proteínas virais, recombinantes e peptídeos sintéticos em suportes sólidos comerciais e modificados por engenharia de superficie. - Giovanna Ivo Andrade (2006)
Bovine herpesvirus 1 (BoHV-1) and Bovine herpesvirus 5 (BoHV-5) are distributed around the world and causes great economic impact, needing hard disease control programs. These viruses share a high homology at nucleotide and aminoacide level. Due to this great similarity few serological methodologies to carry out differential diagnosis that can distinguish both viruses are available. The aim of this work was to develop indirect ELISA assays based on total virus proteins (produced in MDBK cells), glycoprotein G recombinant histidin fused produced inprokaryote system and gC-synthetic peptides produced by F-moc synthesis, for both viruses. Organic-inorganic hybrid material has been developed to improve conventional methods to immobilize biomolecules, enhancing specificity during chemical interactions. The moleculesproduced were attached to solid commercial support and biomaterials modified by engineering surface. Many hybrid materials showed great improvement with enhanced specificity varying from 10 to 60% for bovine herpesvirus serological diagnosis, showing to be a promising tool tobe used in control programs.